How to avoid a retraction in the middle of the horizontal scar and minimize the risk of necrosis in the classic abdominoplasty - Roney Campos; Bruno Victor Barbosa Leoncio Campos (Revista Brasileira de Cirurgia Plástica, 2017)
INTRODUCTION: In classic abdominoplasty, an undesirable result after abdominal flap traction is the occurrence of a suprapubic retraction in the middle of the horizontal scar when it coincides with the superior point of the old umbilical scar. METHODS: Forty-five patients underwent abdominal dermolipectomy associated with liposuction of the entire abdomen and flanks, with decortication of the suprapubic area approximately 5 cm above the initial marking of the incision line, with posterior fixation at the lower border of the abdominal flap. RESULTS: No depressions or necroses were observed in the suprapubic region. CONCLUSION: We observed that the presence of a dermofat flap in the central portion of the suture line in the classic abdominoplasties associated with the complete reconstruction of the surgical planes and the fixation of this flap in the upper abdominal flap avoids the occurrence of depressions in this region, prevents occurrence of necrosis, and improves the quality of the scar by reducing the tensile stress on the tissues.